Valorization of wood chips ash as an eco-friendly mineral admixture in mortar mix design - Pavlíková, Milena; Zemanová, Lucie; Pokorný, Jaroslav; Záleská, Martina; Jankovský, Ondřej; Lojka, Michal; Sedmidubský, David; Pavlík, Zbyšek (Waste management, 2018)
Wood chips ash coming from biomass heating plant is studied as an eco-friendly mineral admixture in mortar mix design. The raw material was mechanically activated by milling in a vibratory disc mill to a degree of fineness comparable to cement. For the mortars with ash dosage, basic physical, mechanical, hygric, and thermal properties is accessed. The mortars with partial Portland cement replacement with wood chips ash exhibited good functional properties for all studied ash dosages. With increasing amount of the ash used, the average pore diameter decreased due to the partial filler effect of WCHA in mortar mix. The strength activity index was very high for all studied mortars and gave evidence of the wood chips ash pozzolanity. The pozzolan effectiveness coefficient varied from 1.52 to 0.59, which proved the pozzolanity of the studied ash and synergic effects in the Portland cement-ash-water system. The results of leaching tests showed, the chlorides contained in ash were safely immobilized in the silicate matrix. The environmental evaluation revealed decrease in both carbon dioxide production and energy consumption by the use of wood chips ash in mortar mix. For the mortar with 20% substitution of Portland cement with wood chips ash, it represents 15% of CO2 and 16% of energy, as compared with the reference mortar mix. As the developed mortars possess good functional and environmental parameters the analyzed wood chips ash can be considered as an eco-efficient low-cost alternative to other pozzolans for production of blended binders.
Keywords: minerály; Minerals; Coal Ash; konstrukční materiály; Biomass; popel uhelný; biomasa; dřevo; Construction Materials; Wood